2018
DOI: 10.25159/2415-5829/2577
|View full text |Cite
|
Sign up to set email alerts
|

Illiteracy among Caregivers: Implications for Children's Educational and Social Development

Abstract: The ability of primary caregivers to provide a healthy, nurturing and stimulating environment for their children is essential for children’s educational advancement and emotional development. However, caregivers who live in the rural areas in South Africa face many challenges, ranging from acute poverty and limited education and skills to feelings of social inadequacy and marginalisation. These factors directly and indirectly affect their ability to care for children and thus these children’s educational progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Over half of these had secondary education with a stable source of income (66.7% in the control group and 84.1% in the intervention group) through formal or self-employment, a situation that could de-emphasize the 'shared' extended family living environment following the financial independence that a source of income presents. 28 In some instances, low literacy levels of primary caregivers affect the ability to provide adequate social support, which could interfere with intended health outcomes. 29 A negative correlation between the caregivers' level of education and the burden of care score has also been reported, implying that the education level of the primary caregiver greatly contributes to their ability to handle stressful situations during caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of these had secondary education with a stable source of income (66.7% in the control group and 84.1% in the intervention group) through formal or self-employment, a situation that could de-emphasize the 'shared' extended family living environment following the financial independence that a source of income presents. 28 In some instances, low literacy levels of primary caregivers affect the ability to provide adequate social support, which could interfere with intended health outcomes. 29 A negative correlation between the caregivers' level of education and the burden of care score has also been reported, implying that the education level of the primary caregiver greatly contributes to their ability to handle stressful situations during caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a culture of book sharing can, at least in part, be ascribed to the fact that most of the parents of the participants in this study were born and raised between 1948 and 1994 – the Apartheid era in South Africa. The capacity of primary caregivers in South Africa (especially those living in rural communities) to provide reading materials for their children is often limited and adversely affected by poverty, limited knowledge and literacy skills (Makunga et al, 2017 ). Of the 40 caregivers who participated in this study, only two reported sharing books with their own caregivers during their childhood.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The reasons for neglecting a more explicit focus on early literacy and language development in majority world countries are multifaceted and complex. When caregivers have limited personal experience of formal schooling, poor understanding of children's literacy and how it is acquired, and low confidence in reading and writing, these aspects may negatively impact children's emergent literacy (Hannon et al, 2019;Makunga et al, 2017;Reutzel and Cooter, 2011;Vally, 2012;Weigel et al, 2006). Diverse cultural groups and languages are also important factors to take into account when considering early literacy outcomes of children (Reese et al, 2012).…”
Section: Introductionmentioning
confidence: 99%